2010
DOI: 10.5539/cis.v4n1p79
|View full text |Cite
|
Sign up to set email alerts
|

Pinch Analysis as a Knowledge Management Tool for Optimization in Supply Chain

Abstract: Supply chain managers are trying to maximize the profitable operation of their manufacturing and distribution supply chain, but due to global competition in process industries and complexities of the supply chain processes together with large computational times, it has made optimization of supply chain management (SCM) quite difficult. Recently, Knowledge management (KM) is a new important information technology-based business paradigm for achieving competitive advantage, and it is no surprise that it has rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Instead of temperature and energy on the axes of the pinch diagram, they plotted the energy demand and CO2 limit. Singvhi et al (2003) and Folorunso et al (2011) demonstrated how pinch analysis can be applied to virtually any product in supply chain management. Instead of heat sources at different temperatures, the pinch analysis includes a curve that represents the production or supply of the product at different points in time.…”
Section: Pinch Analysismentioning
confidence: 99%
“…Instead of temperature and energy on the axes of the pinch diagram, they plotted the energy demand and CO2 limit. Singvhi et al (2003) and Folorunso et al (2011) demonstrated how pinch analysis can be applied to virtually any product in supply chain management. Instead of heat sources at different temperatures, the pinch analysis includes a curve that represents the production or supply of the product at different points in time.…”
Section: Pinch Analysismentioning
confidence: 99%
“…In this study, explicit knowledge of demand and supply from an organization is represented as a composite of pinch analysis. e developed system provides supply chain managers with new insights into SCM, which, in turn, facilitates quick decisionmaking and, in general, contributes to the much-needed competitive advantage [7]. A system is proposed to help define optimization models by regression analysis.…”
Section: Introductionmentioning
confidence: 99%